THE INFLUENCE OF INSTAGRAM ADVERTISING MEDIA, SERVICE QUALITY AND SALES PROMOTION ON CUSTOMER LOYALTY FOR CLASSIC NYOCLATE BEVERAGE PRODUCTS IN TULUNGAGUNG DISTRICT - Supriyono, Supriyono; Haryanti, Nik (Yayasan Education and Social Center, 2023)
The aim of this research is to determine the influence of Instagram advertising media, service quality and sales promotions on customer loyalty for classic chocolate drink products in Tulungagung Regency. The sample in this research was 81 consumers. The sampling technique uses purposive sampling, namely a technique for determining samples with certain considerations. Data analysis uses multiple regression tests. The results of the research show that there is an influence of Instagram advertising media on customer loyalty for Nyoklat Classic drink products in Tulungagung Regency, there is an influence of service quality on customer loyalty for Nyoklat Classic drink products in Tulungagung Regency, there is an influence of sales promotions on customer loyalty for Nyoklat Classic drink products in Tulungagung Regency and There is an influence of Instagram advertising media, service quality and sales promotions on customer loyalty for Nyoklat Classic drink products in Tulungagung Regency.